Prospective Evaluation of Cardiopulmonary Resuscitation Performed in Dogs and Cats According to the RECOVER Guidelines. Part 1: Prognostic Factors According to Utstein-Style Reporting - Hoehne, Sabrina N.; Epstein, Steven E.; Hopper, Kate (Frontiers in Veterinary Science, 2019)
Factors associated with positive cardiopulmonary resuscitation (CPR) outcomes defined according to the veterinary Utstein-style CPR reporting guidelines have not been described since implementation of the Reassessment Campaign on Veterinary Resuscitation (RECOVER) CPR clinical guidelines in 2012. The aims of this study were to assess factors associated with positive CPR outcomes at a U.S. veterinary teaching hospital, to re-evaluate these factors since implementation of the RECOVER guidelines compared to reported factors prior to their publication, and to identify potential additional factors since guideline publication. One-hundred and seventy-two dogs and 47 cats that experienced cardiopulmonary arrest (CPA) and had CPR performed were prospectively included in this observational study. Supervising clinicians were asked to complete a data form on CPR events immediately following completion of CPR efforts. Multivariable logistic regression was used to evaluate the effect of twenty hospital, animal, and arrest variables on the three patient outcomes “any return of spontaneous circulation (ROSC)”, “sustained ROSC”, and survival to hospital discharge. Cats had significantly higher odds to achieve any ROSC (OR (95%CI) 2.72 (1.12-6.61), p=0.028) and survive to hospital discharge than dogs (OR (95%CI) 4.87 (1.52-15.58), p=0.008). Patients had significantly lower odds of achieving any ROSC if CPA occurred during nighttime hours (OR (95%CI) nighttime= 0.52 (0.27-0.98), p=0.043), and higher odds if CPA was witnessed (OR (95%CI) 3.45 (1.57-7.55), p=0.002), if less people were involved in CPR efforts (OR (95%CI) 0.8 (0.66-0.96), p=0.016), if pulses were palpable during CPR (OR (95%CI) 9.27 (4.16-20.63), p<0.0005), and if an IV catheter was already in place at the time of CPA (OR (95%CI) 5.07 (2.12-12.07), p=0.0003). Odds for survival to hospital discharge were significantly higher if less people were involved in CPR efforts (OR (95%CI) 0.65 (0.46-0.91), p=0.013) and for patients of the anesthesia service (OR (95%CI) 14.82 (3.91-56.17), p=0.00007). Overall, factors associated with improved CPR outcomes have remained similar since incorporation of RECOVER guidelines into daily practice. Witnessed CPA events and high-quality CPR interventions were associated with positive patient outcomes, emphasizing the importance of timely recognition and initiation of CPR efforts. An optimal CPR team size has yet to be determined.